2020
DOI: 10.3390/rs12183104
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning for Estimating Rice Chlorophyll Content from In Situ Hyperspectral Data

Abstract: Chlorophyll is an essential pigment for photosynthesis in crops, and leaf chlorophyll content can be used as an indicator for crop growth status and help guide nitrogen fertilizer applications. Estimating crop chlorophyll content plays an important role in precision agriculture. In this study, a variable, rate of change in reflectance between wavelengths ‘a’ and ‘b’ (RCRWa-b), derived from in situ hyperspectral remote sensing data combined with four advanced machine learning techniques, Gaussian process regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 45 publications
(47 reference statements)
5
37
0
Order By: Relevance
“…In this study, the performance of the RF model was comparable to that of the XGBoost model, and this finding is in accordance with the results reported by Herrero-Huerta et al [80]. The RF model outperformed the SVC and ANN models, and the results are similar to those of the studies of An et al, Kayah et al, Xu et al, and Zhu et al [14,[81][82][83], which focused on the performance and accuracy of the RF, SVC, ANN and other models, and the RF model was recommended due to its robustness and accuracy in those studies. Previous studies have indicated that the RF model has the ability to resist overfitting and address high-dimensional data [84], which is why the RF model is an effective model in this study.…”
Section: Comparison Of the Prediction Modelssupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the performance of the RF model was comparable to that of the XGBoost model, and this finding is in accordance with the results reported by Herrero-Huerta et al [80]. The RF model outperformed the SVC and ANN models, and the results are similar to those of the studies of An et al, Kayah et al, Xu et al, and Zhu et al [14,[81][82][83], which focused on the performance and accuracy of the RF, SVC, ANN and other models, and the RF model was recommended due to its robustness and accuracy in those studies. Previous studies have indicated that the RF model has the ability to resist overfitting and address high-dimensional data [84], which is why the RF model is an effective model in this study.…”
Section: Comparison Of the Prediction Modelssupporting
confidence: 92%
“…The satellite remote sensing technique is a unique and useful method for crop biomass monitoring in a repeatable manner due to the valuable information it provides on vegetation parameters, high spatial coverage and long time series, which effectively compensates for the deficiency of traditional biomass estimation methods [2,8,[11][12][13]. Previous studies have revealed that remote sensing is a reliable and effective technique to obtain biophysical and biochemical crop information [6,[14][15][16][17]. For example, the moderate resolution imaging spectroradiometer (MODIS) of the Earth Observation System (EOS) instrument provides long time series observations at a spatial resolution ranging from 250 to 1000 m in multiple spectral bands at the visible to shortwave infrared (SWIR) wavelengths, with a global coverage of one to two days, which has been widely applied in studies on the variation in vegetation parameters at the regional and global scales [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this strategy might have reduced sample size too much to generate regression models, as RF did not perform as well as in previous studies (Biau & Scornet, 2016). A lot of earlier studies have reported the best machine learning algorithms for estimating leaf chlorophyll contents from hyperspectral reflectance or vegetation indices calculated from reflectance (An et al, 2020;Zhu et al, 2020), however, the combinations of machine learning algorithms and wavelength selection methods were not conducted. The results indicated wavelengths selection is a critical step for chlorophyll content estimation and suitable selection methods made estimation accuracies higher.…”
Section: Discussionmentioning
confidence: 84%
“…Pigment concentration measurement by the chemical method takes quite a long time, limiting the ability to analyze a large number of samples, so sub-sampling is used instead. Modern digital technologies allow estimating the pigment concentration in a leaf by the analysis of its reflection spectra (analysis of the hyperspectral images) [16][17][18][19]. Based on such data, plant stress states can be determined [20][21][22] as well as the content of substances of interest, for example, shikimic acid [23].…”
Section: Introductionmentioning
confidence: 99%